Isosteric heats and entropy of adsorption in Henry's law region for carbon and MOFs structures for energy conversion applications - Han, Bo (2022)
The thermodynamic property surfaces such as enthalpy and entropy of an adsorbate + adsorbent systems are essential for designing adsorption-assisted thermal compression, gas storage, separation, and other applications. This paper presents the enthalpy (∆ho) and the entropy (∆so) of the adsorbent-adsorbate system under the barrier of Henry's law region. Hence Henry's law coefficient and Gibbs analogy are applied to formulate the adsorption driving force (∆go). To justify the proposed formulation, the initial adsorption phenomena (at pressure, P → 0) of C2H5OH, CO2, CH4, N2, H2O, R125, R134a, R152a, and R1234yf on graphite/MOFs (such as Zr-MOF-801, Mg-MOF-74, and Al-Fumarate) are considered. It is found that the adsorption driving force is linked with the pore structure of adsorbent materials. We employ experimentally measured isotherms data to calculate the adsorption driving force, ∆go for various adsorbate + activated carbon/MOFs systems. The maximum adsorption driving force is found at the pore widths of 3 Å to 7 Å. The ∆go decreases with higher adsorbent-pore volume and depends on adsorbate molecule size. Employing the proposed driving force concepts, (i) the specific cooing, heating, and COP of the adsorption system, and (ii) the CO2/CH4 storage capacity in the adsorption cell can be projected and analyzed. The adsorption driving force relates to enthalpic and entropic interactions and is useful for the design of adsorbents and the selection of adsorbent-adsorbate pairs for gas storage, separation, and various energy-related applications.